2020
DOI: 10.3390/molecules25143174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Model Compounds on the Rheological Properties of Zein-Based Gels

Abstract: The controlled release of a compound entrapped in a biocompatible formulation is a sought-after goal in modern pharmaceutical technology. Zein is a hydrophobic protein which has several advantageous properties that make it suitable for use as a biocompatible and degradable material under physiological conditions. It is, therefore, proposed for different biomedical and pharmaceutical applications. In particular, due to its gelling properties, it can be used to form a polymeric network able to preserve biomolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Plant-derived polymers occur abundantly in nature and generally exhibit less immunogenicity than polymers of animal origin. Although cellulose, starch, soy protein, and zein, are the most widely used plant-derived polymers, numerous other plant-based polymers have been studied and have shown excellent results in drug delivery research ( George and Suchithra, 2019 ; Iravani and Varma, 2019 ; Gagliardi et al, 2020a , 2020b ).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Plant-derived polymers occur abundantly in nature and generally exhibit less immunogenicity than polymers of animal origin. Although cellulose, starch, soy protein, and zein, are the most widely used plant-derived polymers, numerous other plant-based polymers have been studied and have shown excellent results in drug delivery research ( George and Suchithra, 2019 ; Iravani and Varma, 2019 ; Gagliardi et al, 2020a , 2020b ).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Protein gelation involves denaturation and aggregation processes. In detail, the first phenomenon is based on the perturbation of the native polymer conformation (unfolding), resulting in the exhibition of new reactive sites that are successively exploited in the aggregation step to promote various interactions, novel structures of greater molecular weight and then an ordered network [86,[152][153][154]. As was previously reported in the case of polysaccharides, the variation of several experimental approaches can be used to trigger the unfolding of the protein, such as chemical forces (ionic strength, enzymes) or physical parameters (temperature, pressure) [155,156].…”
Section: Protein-based Hydrogelsmentioning
confidence: 99%
“…Recently, our research team investigated the crucial role exerted by the nature of a compound entrapped in gels made up of 20% w/v of zein [31]. In particular, it was shown that the rheological features, as well as the leakage profile from the tridimensional network, were modulated by the physico-chemical features of the entrapped molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was shown that the rheological features, as well as the leakage profile from the tridimensional network, were modulated by the physico-chemical features of the entrapped molecule. This happened as a consequence of the different interactions occurring between the vegetal protein and the payload, demonstrating the possibility of tailoring the technological properties of the formulation as a function of the required outcome [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation